FREQUENCY OF NEONATAL ATELECTASIS OF THE LUNG AND MORPHOLOGICAL CHANGES - Ruzieva Z. I. (Journal Park Publishing, 2025)
The aim of this study was to address the problems of lung tissue changes in atelectasis. Primary atelectasis of the lungs enters the respiratory distress syndrome and appears as a separate nosological unit. In the article, specific pat morphological signs of primary lung atelectasis are studied. As a material, the lungs of babies who died of atelectasis in the neonatal period were studied microscopically. In the results of the microscopic examination, it was found that the lung tissue has an underdeveloped appearance at first glance. It is observed that the tissue between the alveoli consist of dense tissue and cellular tufts, the blood vessels are wide and full, and it has a structure around which blood clots have appeared. Macrophages, neutrophils and migrated alveolocytes are detected in the alveolar space. After 7-10 days, it is determined that alterative – proliferative processes escalated and turned into atelectatic pneumonia. As a result, pneumosclerosis, bronchiectasis, and the transformation of bronchi into retention cysts are observed. Often, at the site of atelectasis, connective tissue grows and sclerosing develops.
Keywords: Newborn infants, atelectasis, respiratory failure syndrome.